Co-designing climate resilience: advancing drought risk financing in East Africa - Njenga, Geoffrey; Cherotich, Fredah; Paliwal, Ambica (CGIAR, 2025)
The thematic workshop on Next-Generation Earth Observation for Anticipatory Drought Risk Management in East African Pastoral Drylands (N’GOMBE) convened key stakeholders from research institutions, government agencies, the private sector, and development organizations to strengthen collaboration and innovation in drought risk management, product design, and climate risk financing. Held on 3 October 2025 at the International Livestock Research Institute (ILRI), Nairobi, the event brought together 44 participants from government and non-government organizations, the private sector, World Bank, AfDB, and regional bodies like AU-IBAR who engaged in rich knowledge exchange, shared research findings, and deliberated opportunities for co-learning and co-development to advance product innovation and application in the region.